Cloning and expression of industrial important thermostable amylase gene - Sulong, Moohamad Ropaning; Shamsudin, Lokman; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha; Basri, Mahiran (Sarawak Biodiversity Centre, 2008)
Production of thermostable amylases was achieved using local strains. These strains were isolated from various hot springs with water temperatures ranging from 65°C to 90°C. However, a quantitative test of the thermostable amylases using dinitrosalicylic acid (DNSA) method revealed inadequate level of the enzyme production (0.36 U/ml). Therefore, molecular approaches such as cloning and expression were adopted to increase the amount of amylases. The thermostable amylase gene with approaximately 1.6 kb was successfully isolated. The gene was cloned into pET-32b vector and then transformed into E. coli BL21 expression host. The formation of clear zone on starch agar plate proved the presence of the recombinant amylases and thus indicated the success in cloning and expression of thermostable amylase gene. The level of the recombinant thermostable amylase after 24 h of induction time was higher as compared to the wild type (2.3 U/ml). Studies on the optimization of different concentrations of inducer (IPTG) as well as the post induction time are in progress.